2022
DOI: 10.31234/osf.io/j32bn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attentional fluctuations and the temporal organization of memory

Abstract: Event boundaries and temporal context shape the organization of episodic memories. We hypothesized that attentional fluctuations during encoding serve as “events” that shape temporal context representations and recall organization. Individuals encoded trial-unique objects during a modified sustained attention task. Memory was tested with free recall. Response time variability during the encoding tasks was used to characterize “in the zone” and "out of the zone" attentional states. We predicted that: 1) “in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…In contrast, switching task sets at event boundaries represents a procedural working memory update (Oberauer, 2009), which requires a new event model to guide actions in performing the new task. In a similar vein, previous research has found that spontaneous attentional fluctuations during a sustained task do not affect the temporal organization of items during later recall, suggesting that changes in attention alone are not sufficient to create event boundaries when the task remains the same (Jayakumar et al, 2022). Our results provide additional insights into the role of task goals as an important determinant of how experience is organized and segmented in memory.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, switching task sets at event boundaries represents a procedural working memory update (Oberauer, 2009), which requires a new event model to guide actions in performing the new task. In a similar vein, previous research has found that spontaneous attentional fluctuations during a sustained task do not affect the temporal organization of items during later recall, suggesting that changes in attention alone are not sufficient to create event boundaries when the task remains the same (Jayakumar et al, 2022). Our results provide additional insights into the role of task goals as an important determinant of how experience is organized and segmented in memory.…”
Section: Discussionsupporting
confidence: 85%
“…Namely, when one major mental context switches to another, the brain may pass through a transient off-focus (Mittner et al, 2016) or mind-blanking (Mortaheb et al, 2022; Ward & Wegner, 2013) state which is distinct from both processing external stimuli (e.g., movie watching) and engaging in internal thoughts (e.g., memory recall). This account may also explain the difference between within- vs. between-movie boundary patterns: in terms of attentional fluctuation (Jayakumar et al, 2022; Song, Finn, et al, 2021), external attention is enhanced at within-movie event boundaries (Pradhan & Kumar, 2021; Zacks et al, 2007), whereas the relay state is associated with lapses in attention (deBettencourt et al, 2018; Esterman et al, 2014). An alternative, but not mutually exclusive, possibility is that the boundary state involves the recruitment of cognitive control to resolve the competition between mental contexts.…”
Section: Discussionmentioning
confidence: 99%
“…between-movie boundary patterns: in terms of attentional fluctuation (Jayakumar et al, 2022;Song, Finn, et al, 2021), external attention is enhanced at within-movie event boundaries (Pradhan & Kumar, 2021;Zacks et al, 2007), whereas the relay state is associated with lapses in attention (deBettencourt et al, 2018;Esterman et al, 2014). An alternative, but not mutually exclusive, possibility is that the boundary state involves the recruitment of cognitive control to resolve the competition between mental contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The available data are not encouraging. In two studies, Mulligan et al (2016Mulligan et al ( , 2021 in attention over time also may have little effect on temporal context memory (Jayakumar et al, 2022). It is possible that the transient nature of responses in the continuous dual-task paradigm boosts episodic memory while having little effect on the formation of inter-item associations (cf.…”
Section: How the Abe Relates To The Effects Of Event Boundaries On Ep...mentioning
confidence: 96%